2017
DOI: 10.21873/anticanres.11940
|View full text |Cite
|
Sign up to set email alerts
|

Metallothionein Isoform Expression in Benign and Malignant Thyroid Lesions

Abstract: Expression of functional MT isoforms may contribute to thyroid carcinogenesis and potentially serve as a diagnostic marker in distinguishing benign and malignant lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Some studies have shown that increased expression of MT is associated with a higher proliferative potential in various types of cancer and a more rapid disease progression, as well as cellular resistance to chemotherapy and radiotherapy 15,16 . However, there is a paucity of studies evaluating the immunohistochemical expression of MT in breast cancer, and to the best of our knowledge, only one published study in the literature has compared the expression of MT-1 between women with breast cancer and women with fibroadenoma 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that increased expression of MT is associated with a higher proliferative potential in various types of cancer and a more rapid disease progression, as well as cellular resistance to chemotherapy and radiotherapy 15,16 . However, there is a paucity of studies evaluating the immunohistochemical expression of MT in breast cancer, and to the best of our knowledge, only one published study in the literature has compared the expression of MT-1 between women with breast cancer and women with fibroadenoma 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Beata Wojtczak et al. ( 32 ) has found that metallothioneins (MTs) are involved in many cellular processes, such as the binding and transport of zinc and copper ions, and the expression of functional MT genes may contribute to thyroid carcinogenesis. Jorge Gaspar et al.…”
Section: Discussionmentioning
confidence: 99%
“…17 Its protein product is a low-molecular weight, cysteine-rich protein that acts as a scavenger of free radicals and heavy metals. 17 Aberrant expression of the MT1F gene has been linked to various human cancers, including colon cancer, 18 hepatocellular carcinoma, 19 and gastric cancer, 20 suggesting its potential role in cancer development and progression. However, the above two genes have not been studied as specific markers of ECs.…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrate that CA4 may serve as a diagnostic biomarker and potential therapeutic target in GC by inhibiting cellular proliferation via regulating the expression of cell cycle‐associated proteins. The MT1F gene is a member of the metallothionein (MT) gene family 17 . Its protein product is a low‐molecular weight, cysteine‐rich protein that acts as a scavenger of free radicals and heavy metals 17 .…”
Section: Discussionmentioning
confidence: 99%